Feasibility and Effectiveness of an Individualized 12-Week "Uptime" Participation (U-PART) Intervention in Girls and Women With Rett Syndrome. Issue 1 (4th October 2019) - Stahlhut, Michelle; Downs, Jenny; Wong, Kingsley; Bisgaard, Anne-Marie; Nordmark, Eva
Abstract: Background: Girls and women with Rett Syndrome (RTT) have low levels of daily physical activity and high levels of sedentary time. Reducing sedentary time and enhancing "uptime" activities, such as standing and walking, could be an important focus for interventions to address long-term health and quality of life in RTT. Objective: The aim of the study was to evaluate the feasibility and health-related effects of an individualized 12-week uptime participation (U-PART) intervention in girls and women with RTT. Design: The study used a single-group pretest-posttest design with 4 assessments (2 baseline, postintervention, and follow-up). Methods: A participation-based intervention employing a whole-day approach was used. During a 12-week intervention period, individualized programs focused on participation in enjoyable uptime activities in home, school/day center, and community settings. Feasibility was assessed with a study-specific questionnaire. Primary outcome measures were sedentary time and daily step count. Secondary outcomes were gross motor skills, walking capacity, quality of life, and goal attainment scaling. Results: Fourteen girls and women who were 5 to 48 years old and had RTT participated. The U-PART intervention was perceived as feasible by caregivers. Similar scores were observed at baseline assessments in all outcomes. Positive effects with small to medium effect sizes (0.27–0.54) were seen in sedentary time (− 4%), daily step count (+ 689 steps/d), walking capacity (+ 18.8 m), quality of life (+ 2.75 points), and goal attainment scaling after the intervention. Positive effects were maintained in sedentary time (− 3.2%) and walking capacity (+ 12.1 m) at short-term follow-up. Limitations: This study was limited by the lack of a control group. However, participants acted as their own control, and the stable baseline period partially mitigated this issue. Conclusions: The U-PART intervention was found to be feasible and effective in the short term in girls and women with RTT.